Interactive Dialogics and Accuracy Of Physics LKPD Materials Based on PBL to Improve Student’s Critical Thinking Skills in Business And Energy Materials - Wahyuni, Nilta; Prastyaningrum, Violin Candra; Sari, Dwi Resta Maulita; Iswardani, Fadia Arisma; Bisyri, Ahmad Janukhi; Hidayah, Hikmah; Mahardika, I Ketut; Subiki, Subiki (ANTHOR: Education and Learning Journal, 2023)
The concept of effort is closely related to the concept of energy. Energy can be interpreted as the cause of effort. However, effort can also cause energy changes. The purpose of this study was to determine how the motivation ability and accuracy of PBL-based Physics LKS improve students' critical thinking on the material of effort and energy. This study used a research and development planning methodology. The data collection technique used is avalidation sheet as a validator. In addition, to obtain relevant information about the assessment tool, use analysis techniques, calculation methods to calculate the average score of each component and literature research. Based on the results of the research assessed by material experts and media experts, PBL-based LKS on the material of effort and energy and its use in everyday life is in the appropriate category and this PBL-based LKS can alsoincrease student learning motivation, where they can be more interactive in understanding the material of effort and energy and can think critically. Students can also solve problems about effort and energy material well. The conclusion obtained in this study is that the quality of this LKPD meets very good criteria so that this LKPD can be declared valid and of high quality to be used as one of the teaching materials for high school physics of work and energy. This LKPD has produced teaching materials that are quite accurate.